2017
DOI: 10.1093/mnras/stx2034
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary sequence of post-starburst galaxies

Abstract: There are multiple ways in which to select post-starburst galaxies in the literature. In this work, we present a study into how two well-used selection techniques have consequences on observable post-starburst galaxy parameters, such as colour, morphology and environment and how this affects interpretations of their role in the galaxy duty cycle. We identify a master sample of Hδ strong (EW Hδ > 3Å) post-starburst galaxies from the value-added catalogue in the 7th data release of the Sloan Digital Sky Survey (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…The preference for shorter star-forming timescales towards higher environmental densities necessarily implies a higher incidence of poststarburst galaxies in these denser environments. In the local universe post-starburst galaxies have been shown to predominantly reside in low density environments (e.g., Zabludoff et al 1996;Hogg et al 2006;Wilkinson et al 2017;Pawlik et al 2018); however, this trend reverses at higher redshifts (z 0.4) wherein post-starbursts are more commonly found in higher-density environments (e.g., Dressler et al 1999;Poggianti et al 2009;Yan et al 2009;Muzzin et al 2012;Wu et al 2014;Lemaux et al 2017). Two of these studies (Wu et al 2014;Lemaux et al 2017) are based on specific large scale structures included in the present work.…”
Section: Fitting the Model To Observationsmentioning
confidence: 83%
“…The preference for shorter star-forming timescales towards higher environmental densities necessarily implies a higher incidence of poststarburst galaxies in these denser environments. In the local universe post-starburst galaxies have been shown to predominantly reside in low density environments (e.g., Zabludoff et al 1996;Hogg et al 2006;Wilkinson et al 2017;Pawlik et al 2018); however, this trend reverses at higher redshifts (z 0.4) wherein post-starbursts are more commonly found in higher-density environments (e.g., Dressler et al 1999;Poggianti et al 2009;Yan et al 2009;Muzzin et al 2012;Wu et al 2014;Lemaux et al 2017). Two of these studies (Wu et al 2014;Lemaux et al 2017) are based on specific large scale structures included in the present work.…”
Section: Fitting the Model To Observationsmentioning
confidence: 83%
“…Other studies have reported non-merging galaxy-galaxy interactions are more likely to maintain spiral structure post starburst (Cales et al 2013;Wilkinson et al 2017). There are an extensive number of studies researching the link between mergers and starbursts but to what extent do non-merging interactions play on triggering starbursts?…”
Section: Triggering Mechanisms Of Starburstsmentioning
confidence: 99%
“…Selecting galaxies in one snapshot simplifies the analysis as the time between snapshots is not uniform. Working in a low-z regime allows for the minimum time difference between snapshots, allowing us to monitor the evolution of low-z galaxies more closely and provides ease of comparison to SDSS studies like Wilkinson et al (2017).…”
Section: Starburst Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In galaxies that may be otherwise determined to be passive, the presence of an inverted H:K ratio serves as a signpost to its recent star-forming past that might otherwise go undetected through the use of classifications derived from more common analyses such as [Oii] in concert with Hδ (and/or further Balmer lines; cf. Blake et al 2004;Wilkinson et al 2017) and may offer an additional method or cut to apply to a sample to identify a transitioning post-starburst galaxy (cf. Pawlik et al 2018;Wild et al 2009).…”
Section: Heterogeneitymentioning
confidence: 99%